Semi-quantitative analysis of the effects of cyclosporine on remyelination following gliotoxic injection in the brainstem - E F Bondan; M F M Martins; A M C Branco; M A Lallo (Arquivos de Neuro-Psiquiatria)
The use of cyclosporine (CsA) has shown to induce an increase in the density of oligodendrocytes near remyelinating areas following the injection of ethidium bromide (EB), a demyelinating agent, in the rat brainstem. This study was designed in order to evaluate if CsA has the capacity of increasing remyelination. In this context, a comparison between the final balance of myelin repair in CsA treated and non-treated rats was assessed using a semi-quantitative method developed for documenting the extent and nature of remyelination in gliotoxic lesions. Wistar rats were submitted to intracisternal injection of 10 microliters of 0.1% EB. Some were treated during 31 days with CsA (group III - 10 mg/kg/day by 7 days and, thereafter, 3 times a week, with a minimal interval of 48 hours) by intraperitonial route. Others were not treated with CsA (group I). A control group was planned receiving into the cisterna pontis 10 microliters of 0.9% saline solution and following after that the same CsA administration protocol (group II). Results clearly demonstrate that in vivo administration of CsA after EB-demyelinating lesions stimulated oligodendrocyte remyelination (mean remyelination scores of 3.72±0.25 for oligodendrocytes and 1.04±0.39 for Schwann cells) compared to non-treated animals (3.13±0.71 and 1.31±0.62, respectively), although the mechanisms by which this positive CsA effect occurs are unclear.